Should All Living Kidney Donors Receive Donor Health Insurance? - Ethical Guidance for Evaluating Policies and Actions that Provide Financial Benefits to Living Organ Donors - Johan C Bester; Stuart M. Flechner; Matt Ronin; Garet Hil (Journal of Organ Transplantation, 2018)
This review article provides ethical guidance for determining which kinds of financial benefits provided to living organ donors are ethically appropriate. It does so by way of ethical analysis of a policy case study: the National Kidney Registry (NKR) has implemented a donor insurance program to all its living donors. Is such a policy ethically supportable, or is it an unethical practice? The article proceeds as follows. First, a framework for grounding the ethical commitments of transplant programs is defended. It is argued that this framework can be accepted by all who work in transplant medicine, regardless of differences in ethical theory preference or background. Second, from this framework two ethical principles are formulated. (1) Living donors should, as far as possible, not be worse off for donating. (2) Disincentives towards donation should be removed as much as possible. Third, issues with unethical incentives are explored: undue inducement, commodification of the body, potential decreased organ donation rates, and potential exploitation of vulnerable populations. Lastly, these ethical considerations are applied to the policy change at the NKR, showing that the NKR policy change appears to be ethically supportable. Financial benefits provided to donors are ethically sound if they are in keeping with principles (1) and (2), and do not cause undue inducement, commodification, decreased organ donation, or exploitation. It is ethically appropriate for transplant programs to institute as well as study such programs with the goal of serving the welfare and interests of patients, donors, and the general public.
Keywords: Living Organ Donors